2020
DOI: 10.1093/europace/euaa271
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and efficacy of left bundle branch area pacing in patients indicated for cardiac resynchronization therapy

Abstract: Aims The present study was to evaluate the feasibility and clinical outcomes of left bundle branch area pacing (LBBAP) in cardiac resynchronization therapy (CRT)-indicated patients. Methods and results LBBAP was performed via transventricular septal approach in 25 patients as a rescue strategy in 5 patients with failed left ventricular (LV) lead placement and as a primary strategy in the remaining 20 patients. Pacing paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 20 publications
1
44
0
Order By: Relevance
“…In our updated systematic review and meta-analysis of eight non-randomized studies, we examined the clinical outcomes of LBBAP from a pool of 527 patients with CRT indications. 9,11,[17][18][19][20][21][22] In contrast to Zhong et al, our study reported a detail analysis on the clinical outcomes of QRS duration, LVEDD, LVEF, and NYHA class from the four studies with comparison groups (between the LBBAP and BVP groups). 11,17,18,21 We also performed a pooled analysis from the eight studies on the clinical outcomes of LBBAP for CRT in patients with LBBB.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…In our updated systematic review and meta-analysis of eight non-randomized studies, we examined the clinical outcomes of LBBAP from a pool of 527 patients with CRT indications. 9,11,[17][18][19][20][21][22] In contrast to Zhong et al, our study reported a detail analysis on the clinical outcomes of QRS duration, LVEDD, LVEF, and NYHA class from the four studies with comparison groups (between the LBBAP and BVP groups). 11,17,18,21 We also performed a pooled analysis from the eight studies on the clinical outcomes of LBBAP for CRT in patients with LBBB.…”
Section: Discussionmentioning
confidence: 93%
“… 21 Prospective, observational, single-centre LBBAP vs BVP LBBB defined according to Strauss criteria, NYHA functional class II-IV with LVEF ≤ 35% 45 Primary LBBAP, * n = 24 Implant success, n = 21 (87.5%) Primary BVP, n = 21 6 Li et al. 22 Prospective, observational, single-centre LBBAP only NYHA functional class II-IV with LVEF < 50% (LBBB, n = 14; RBBB, n = 3; IVCD, n = 4; RVP, n = 4) 25 Primary LBBAP, * n = 20 Rescue LBBAP, † n = 5 Implant success, not reported NA Mean 9.1 ± 5.1 Vijayaraman et al 20 Retrospective, observational, multicentre LBBAP only NYHA functional class II-IV, baseline LVEFs ≤ 50%, and indications for ventricular pacing and/or CRT (LBBB, n = 126; RBBB, n = 54; IVCD, n = 49; RVP, n = 48, narrow, n = 48) 325 A mix of primary LBBAP * and rescue LBBAP † , and LBBAP § , n = 325 Implant success, n = 277 (85.2%) NA Mean 6 ± 5 Huang et al. 9 Prospective, observational, multicentre LBBAP only Complete LBBB, nonischemic cardiomyopathy, symptomatic heart failure with LVEF < 50% 63 Rescue LBBAP, § n = 63 Implant success, n = 61 (96.8%) NA Mean 18 (range, 15 to 20) Zhang et al.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations